USE OF GAMIFICATION ELEMENTS IN TEACHING MATHEMATICAL ANALYSIS AT HIGHER EDUCATION INSTITUTIONS - Linnik, Hanna; Morachkovska, Iryna (Physical and Mathematical Education, 2026)
The article presents the results of a study on the effectiveness of gamification elements in teaching Mathematical Analysis at the National Technical University “Kharkiv Polytechnic Institute”. The research focuses on assessing the impact of gamified approaches on students’ learning motivation, cognitive engagement, and the quality of their mastery of theoretical material among engineering students.Formulation of the problem. Modern teaching of mathematical disciplines is characterized by a high level of abstraction, which often leads to decreased student motivation and superficial knowledge acquisition. In the context of the digitalization of the educational environment, there is a growing need to identify effective didactic tools that activate students’ learning activities. This paper addresses the problem of the feasibility and effectiveness of implementing gamification in the teaching of mathematical analysis.Materials and methods. Within the study, an original didactic game, entitled Mathematical Associations, was developed and implemented during practical classes in mathematical analysis. The experimental base consisted of first-year undergraduate student groups. The research employed pedagogical observation, questionnaires, analysis of students’ learning activity, and assessment of task performance. Digital tools from Office 365 were used to organize feedback and collect responses.Results. The results indicate increased student engagement in the learning process, greater interest in the course, and improved understanding of the key topics in mathematical analysis. Enhanced communication within academic groups and increased learning activity among the majority of participants were observed. At the same time, a small proportion of students expressed a preference for traditional teaching methods.Conclusion. The results of the study confirm the effectiveness of gamification in teaching mathematical analysis to increase learning motivation, develop communication skills, and stimulate students’ cognitive activity. The findings may be used for further research and for implementing gamified approaches in teaching other mathematical disciplines.
Keywords: gamification; mathematical analysis; learning; motivation